1990
DOI: 10.1007/bf02244230
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam changes risk assessment in an anxiety/defense test battery

Abstract: An anxiety/defense test battery was designed to assess defensive reactions of laboratory rats to situations associated with nonpainful threat (exposure to a cat). The battery measured three defense patterns, movement inhibition, risk assessment behaviors, and inhibition of nondefensive behaviors, in two tasks. Diazepam (4.0 mg/kg) altered four of five risk assessment measures, but failed to show an anxiolytic effect on movement inhibition, and had minimal and inconsistent effects on inhibition of nondefensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
38
2
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 149 publications
(57 citation statements)
references
References 27 publications
12
38
2
3
Order By: Relevance
“…The substantial agreement with this profile of effects for 5-HT 1A agonists, some of which had been utilized clinically as anxiolytics (Jacobson et al, 1985), supported this view, as did findings that alcohol produced similar patterns of risk assessment and (at higher doses) reduced defensive threat/attack, albeit with a paradoxical low dose enhancement of the latter (Blanchard et al, 1990a(Blanchard et al, , 1992. Ritanserin, a 5-HT 2A /5-HT 2C receptor antagonist, reduced risk assessment in the cat odor situation but was without effect on other Anxiety/Defense Test Battery measures.…”
Section: The Anxiety/defense Test Batterymentioning
confidence: 55%
“…The substantial agreement with this profile of effects for 5-HT 1A agonists, some of which had been utilized clinically as anxiolytics (Jacobson et al, 1985), supported this view, as did findings that alcohol produced similar patterns of risk assessment and (at higher doses) reduced defensive threat/attack, albeit with a paradoxical low dose enhancement of the latter (Blanchard et al, 1990a(Blanchard et al, , 1992. Ritanserin, a 5-HT 2A /5-HT 2C receptor antagonist, reduced risk assessment in the cat odor situation but was without effect on other Anxiety/Defense Test Battery measures.…”
Section: The Anxiety/defense Test Batterymentioning
confidence: 55%
“…The phenomenon is consistent with a reduced anxiety-like behavior (ie, increase center time) and increased locomotor exploration (ie, increase horizontal and vertical activities). It has been demonstrated that in exploration-based tests for anxiety-like behaviors, such as the light-dark exploration or emergence tests, animals with anxiety would rather spend more time in the dark compartment (Blanchard et al, 1990;File, 2001;Holmes et al, 2003b). In light-dark exploration tests, the GAT1 À/À mice showed more transitions between light and dark compartments and spent more time in the light compartment than GAT1 + / + mice.…”
Section: Discussionmentioning
confidence: 99%
“…In exploration-based tests for anxiety-like behavior, such as the light2dark exploration or emergence tests, it can be difficult to dissociate a strong anxiety-like phenotype from an impairment in exploratory locomotion per se, as both can manifest as an inhibition of exploratory locomotion (Blanchard et al, 1990;Crawley, 2000;File, 2001;Holmes, 2001;McNaughton and Gray, 2000). In this context, 5-HTT À/À mice were no different from +/+ controls on independent measures of locomotor activity (ie entries and rears in the protected closed arms) in the elevated plus maze, under baseline conditions.…”
Section: Discussionmentioning
confidence: 99%